High Oxygen Exchange Activity of Pristine La0.6Sr0.4FeO3–δ Films and Its Degradation. Issue 12 (14th August 2020) - Schmid, Alexander; Nenning, Andreas; Opitz, Alexander; Kubicek, Markus; Fleig, Jürgen
Abstract : The polarization resistance of La0.6 Sr0.4 FeO3– δ (LSF) thin film electrodes was investigated by electrochemical impedance spectroscopy. Different states were considered, ranging from pristine films right after deposition to films degraded under various conditions. Impedance measurements performed inside the pulsed laser deposition chamber (in-situ) revealed the existence of a very facile, low resistive state of as-deposited thin films with up to two orders of magnitude lower resistances compared to conventional ex-situ measurements and literature data. Ex-situ and in-situ measurements show different p O 2 dependencies of polarization resistances, suggesting a different oxygen exchange reaction mechanism on the as-deposited films. The time dependence of the polarization resistance indicates that two degradation mechanisms with different timescales are responsible for the much higher resistances found in ex-situ measurements. Degradation mechanisms are discussed and conclusions with respect to the rate determining step of oxygen exchange on different surfaces are drawn.